Long-Term Effects of Maternal Low-Protein Diet and Post-weaning High-Fat Feeding on Glucose Metabolism and Hypothalamic POMC Promoter Methylation in Offspring Mice - Zheng, Jia; Zhang, Ling; Liu, Jiayi; Li, Yanli; Zhang, Junqing (Frontiers in Nutrition, 2021)
Substantial evidence indicated that maternal malnutrition could increase the susceptibility to obesity, insulin resistance and type 2 diabetes in adulthood. It is increasingly apparent that the brain, especially the hypothalamus, plays critical roles in glucose homeostasis. However, little information is known about the mechanisms linking maternal protein restriction combined with post-weaning high-fat feeding with altered expression of brain neurotransmitters, and investigations into the epigenetic modifications of hypothalamus in offspring have not been fully elucidated. Our objective was to explore the effects of maternal protein restriction combined with post-weaning high-fat feeding on glucose metabolism and hypothalamic POMC methylation in male offspring mice. C57/BL6 mice were fed on either low-protein (LP) or normal chow (NC) diet throughout gestation and lactation. Then, the male offspring were randomly weaned to either NC or high-fat (HF) diet until 32 weeks of age. Gene expressions and DNA methylation of hypothalamic proopiomelanocortin (POMC) and melanocortin receptor 4 (MC4R) were determined in male offspring. The results showed that birth weights and body weights at weaning were both significantly lower in male offspring mice of the dams fed a low-protein diet. Maternal protein restriction combined with post-weaning high-fat feeding, predisposes higher body weight, persistent glucose intolerance (from weaning to 32 weeks of age), hyperinsulinemia and hyperleptinemia in male offspring mice. POMC and MC4R expressions were significantly increased in offspring mice fed with maternal low-protein and postnatal high-fat diet (P<0.05). Furthermore, maternal protein restriction combined with post-weaning high-fat feeding induced hypomethylation of POMC promoter in the hypothalamus (P<0.05) and POMC-specific methylation (%) was negatively correlated with the glucose response to a glucose load in male offspring mice (r = −0.42, P = 0.039). In conclusion, maternal low-protein diet combined with post-weaning high-fat feeding predisposed the male offspring to impaired glucose metabolism and hypothalamic POMC hypomethylation. These findings can advance our thinking about hypothalamic POMC gene methylation between maternal low-protein diet combined with post-weaning high-fat feeding and metabolic health in offspring.